Population genetics and mitochondrial genomics of the critically endangered Philippine eagle Pithecophaga jefferyi - Luczon,Adrian U.; Quilang, Jonas P. (Quezon City Institute of Biology, College of Science, University of the Philippines Diliman, 2013)
The Philippine Eagle Pithecophaga jefferyi (Aves, Accipitridae) is a diurnal raptor that is endemic to the Philippines. Its distribution includes the islands of Luzon, Samar, Leyte and Mindanao. The Philippine Eagle is a critically endangered species under the IUCN Red List, with a high end estimated population of only 500 breeding pairs existing in the wild. Their population decline has been attributed to unabated hunting and diminish in forest areas in the country, particularly since the mid-1900s. Information from molecular studies would aid in the conservation of this species; however, such studies are currently limited. In this study, the mitochondrial genome of this species was sequenced and the genetic structure of its present population was determined.
Thesis (M.S.-Biology)--University of the Philippines Diliman
Keywords: Eagles -- Philippines; Endangered species -- Philippines